On b-I-Open Sets and b-I-Continuous Functions - Metin Akdağ (International Journal of Mathematics and Mathematical Sciences)
We studied some more properties of b-I-open sets and obtained several characterizations of b-I-continuous functions which are introduced by Caksu Guler and Aslim (2005). We also investigated their relationship with other types of functions.